Interpreting the Global Enteric Multicenter Study (GEMS) Findings on Sanitation, Hygiene, and Diarrhea - Crocker, Jonny (PLoS Med, 2016)
In this Perspective on the GEMS study by Kelly Baker and colleagues, Jonny Crocker and Jamie Bartram consider the implications of associations found and not found between diarrheal disease and sanitation and hygiene.